(untitled) (Journal of Contemporary Philology, 2025)
In this article, I investigate the sociolinguistic factors that influenced the word order in nominal phrases in the South Slavic dialects that are spoken in Albania, with a specific focus on the impact of Albanian. Utilizing data from the Corpus of Slavic Dialects in Albania, I examined variations in adjective placement (pre- or post-noun) across several dialects – Golloborda Macedonian (GM), Korça Macedonian (KM), Prespa Macedonian (PM), and migrational Štokavian dialects from Shijak (SŠ) and Myzeqe (MŠ). The analysis revealed that the Albanian-influenced Noun-Adjective order (NADJ) was increasing in these dialects, and was mainly influenced by age, gender, residence type (rural versus urban), and type of community dwelling (compact versus dispersed). The stability of the conservative Adjective Noun (ADJN) order in compact communities and older generations in contrast to the increased Albanian-influenced NADJ usage among younger speakers and by those in dispersed communities, was particularly notable. The influence of standard Slavic languages may reverse the process by supporting the conservative ADJN word order. These findings contribute to the research on the areal spread of word order patterns.